2011
DOI: 10.4103/0019-557x.82539
|View full text |Cite
|
Sign up to set email alerts
|

A study on visual outcomes after cataract surgery with intraocular lens implants at the rural health training center, Paithan, Maharashtra

Abstract: A study was conducted to assess the visual outcomes of patients after cataract surgery with intraocular lens implants with reference to visual acuity (VA) and visual function (VF) and to assess patient satisfaction with surgical outcome. The retrospective study was carried out using operation theatre records at the Rural Health Training Centre (RHTC), Paithan, during 2007. Out of 819 cataract surgery patients operated in 2007 a total of 50 were selected randomly. Door-to-door visits were paid by investigator a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
2
4
1
Order By: Relevance
“…24 That we saw relatively better outcomes in our study might be due to the fact that the majority of surgeries were performed by senior ophthalmologists and the final vision assessment being at 6-8 weeks (versus 1-4 weeks for two-thirds of patients in the Gondar study). The outcomes in our study were generally better than those from a study in India, where fair outcomes were achieved in only 50% of cases 25 and also compared to a study from Nepal, where good, borderline and poor visual outcomes were found in 41.3%, 45%, and 13.7%, respectively. 26 An additional study from Malawi demonstrated poor outcomes in 19.5% of cases, a number much higher that found in our study.…”
contrasting
confidence: 62%
“…24 That we saw relatively better outcomes in our study might be due to the fact that the majority of surgeries were performed by senior ophthalmologists and the final vision assessment being at 6-8 weeks (versus 1-4 weeks for two-thirds of patients in the Gondar study). The outcomes in our study were generally better than those from a study in India, where fair outcomes were achieved in only 50% of cases 25 and also compared to a study from Nepal, where good, borderline and poor visual outcomes were found in 41.3%, 45%, and 13.7%, respectively. 26 An additional study from Malawi demonstrated poor outcomes in 19.5% of cases, a number much higher that found in our study.…”
contrasting
confidence: 62%
“…These observations are in agreement with the results reported in previous studies, where the majority of study participants presented with reduced VRQoL pre-surgery. 1,17,35 For example, Bandhu et al 17 reported that 70% of their study participants presented with reduced VRQoL pre-surgery. Similarly, Domple et al 35 reported that all their study participants presented with reduced and/or poor VRQoL pre-surgery.…”
Section: Demographic Characteristicsmentioning
confidence: 96%
“…1,17,35 For example, Bandhu et al 17 reported that 70% of their study participants presented with reduced VRQoL pre-surgery. Similarly, Domple et al 35 reported that all their study participants presented with reduced and/or poor VRQoL pre-surgery. As observed in this study, the presence of cataract was associated with a decrease in the quality of life for the questions in all three domains, which corroborates the finding that vision impairment is associated with decreased VRQoL pre-surgery.…”
Section: Demographic Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…Intraocular pressure range is 11 -21 mm Hg in the normal eye when measured with an applanation tonometer. 2 Intraocular pressure is known to have diurnal fluctuation. 3 It is also affected by the temperature, season, exercise, blood pressure, respiration and medicine intake for ocular and systemic diseases.…”
Section: Introductionmentioning
confidence: 99%